LANGUAGE OF INSTRUCTION AND LEARNING OUTCOMES: THE STATE OF RESEARCH - Izuagba, Angela C. (Sokoto Educational Review, 2020)
The effects of languages of instruction on learning outcomes have bothered linguists and educational psychologists since the inception of formal education. These scholars are determined to identify the language of instruction that enhances learning outcome. The findings of these research works are the focus of this paper, as it tries to relate the findings to some of the problems that confront learners in Nigeria. One major revelation of the exposition is that there is an inextricable relationship between cognitive developments; cognitive functions; academic attainment and the language of school instruction. Based on this some recommendations were made among which is the teaching of English as an additional language rather than its use as a language of instruction in the primary and secondary school levels.